Developing Academic Writing Module to Reduce Plagiarism - Hilma Suryani; Eka Apriani (STAI Hubbulwathan Duri, 2021)
Plagiarism has become a stressful problem in the academic world. In higher education, students must write a scientific paper that is free from plagiarism. Many referencing styles are offered to enable the writers to produce the proper scientific works. This study aimed to produce a module on academic writing for English department students. The module focused on writing citations based on APA style references, including in-text citation, paraphrasing, and summarizing. It was a research and development study that involved fifth-semester students. The samples were selected purposively. The data were collected by using interviews, questionnaires, and tests to see the product's validity, practicality, and effectiveness. The data gathered were analyzed qualitatively and quantitatively. Based on the study results, it was found that the validity of the product showed a very high category (0.92). Practicality consists of three aspects, ease, efficiency, and usefulness, categorized very high at small groups (0.85) and field tests (0.87). The module's effectiveness was seen from the gain score, which is 0.4. This score indicated the medium progress made by the students after having the treatment.